Comparative transcriptome analysis of human skeletal muscle in response to cold acclimation and exercise training in human volunteers - Emmani B. M. Nascimento; Roland W. J. Hangelbroek; Guido J. E. J. Hooiveld; Joris Hoeks; Wouter D. Van Marken Lichtenbelt; Matthijs H. C. Hesselink; Patrick Schrauwen; Sander Kersten (BMC, 2020)
Abstract Background Cold acclimation and exercise training were previously shown to increase peripheral insulin sensitivity in human volunteers with type 2 diabetes. Although cold is a potent activator of brown adipose tissue, the increase in peripheral insulin sensitivity by cold is largely mediated by events occurring in skeletal muscle and at least partly involves GLUT4 translocation, as is also observed for exercise training. Methods To investigate if cold acclimation and exercise training overlap in the molecular adaptive response in skeletal muscle, we performed transcriptomics analysis on vastus lateralis muscle collected from human subjects before and after 10 days of cold acclimation, as well as before and after a 12-week exercise training intervention. Results Cold acclimation altered the expression of 756 genes (422 up, 334 down, P < 0.01), while exercise training altered the expression of 665 genes (444 up, 221 down, P < 0.01). Principal Component Analysis, Venn diagram, similarity analysis and Rank-rank Hypergeometric Overlap all indicated significant overlap between cold acclimation and exercise training in upregulated genes, but not in downregulated genes. Overlapping gene regulation was especially evident for genes and pathways associated with extracellular matrix remodeling. Interestingly, the genes most highly induced by cold acclimation were involved in contraction and in signal transduction between nerve and muscle cells, while no significant changes were observed in genes and pathways related to insulin signaling or glucose metabolism. Conclusions Overall, our results indicate that cold acclimation and exercise training have overlapping effects on gene expression in human skeletal muscle, but strikingly these overlapping genes are designated to pathways related to tissue remodeling rather than metabolic pathways.